Cloning of the glucocorticoid receptor (GR) in gilthead seabream (Sparus aurata) - Acerete, L. (2014)
In order to determine the cortisol response after an immune challenge in the gilthead seabream (Sparus aurata), a cortisol receptor (GR) was cloned, sequenced and its expression determined after lipopolysaccharide (LPS) treatment. To clone the gilthead seabream GR (sbGR), consecutive PCR amplifications and screening of a pituitary cDNA library were performed. We obtained a clone of 4586 bp encoding a 784aa protein. Northern blot analysis from head kidney, heart and intestine revealed that the full length sbGR mRNA was approximately 6.5 Kb. A LPS treatment, used as an acute stress model, was employed to characterise the expression of sbGR and some selected genes involved in the immune response (IL-1β, TNF-α, Mx protein, cathepsin D and PPAR-γ). All genes were expressed in all tissues examined and responses were tissue and time dependent revealing differential gene expression profiles after LPS administration. Furthermore, analysis of plasma cortisol levels after LPS injection, showed an acute response to inflammatory stress with a significant increase two and six h after injection, recovering to basal levels 12 h post-stress in all LPS concentrations tested.